PENGARUH KOMPETENSI GURU DAN MOTIVASI INSTRINSIK TERHADAP KINERJA GURU DI SMA NEGERI KECAMATAN SEMBAWA KABUPATEN BANYUASIN - Radeka, Agun; Putra, Alhadi Yan; Destiniar, Destiniar (STKIP Pesisir Selatan, 2024)
The purpose of carrying out this research is 1) To determine the effect of competency on teacher performance at State High School, Sembawa District, Banyuasin Regency; 2) To determine the effect of intrinsic motivation on teacher performance at State High School, Sembawa District, Banyuasin Regency; 3) To determine the influence of competency and intrinsic motivation on teacher performance at State High School, Sembawa District, Banyuasin Regency. This research was carried out at Sembawa District Public High School with a research sample of 97 teachers. Data collection techniques were carried out through observation, documentation studies and distributing questionnaires. The validity test uses construct validity, while the reliability test uses Cronbach's Alpha. Linearity Test and Normality Test. The results of this research are that: 1) There is a partially significant influence between teacher competency on teacher performance in Sembawa District Public High School, Banyuasin Regency, where t = 3.284 > from t table 1.671; 2) There is a partially significant influence between intrinsic motivation on teacher performance at SMA Negeri Sembawa District, Banyuasin Regency, where t = 3.151 > from t table 1.671; 3) There is a simultaneous influence between teacher competence and intrinsic motivation on teacher performance in Sembawa District Public High School, Banyuasin Regency where the calculated f value = 6.112 > more than f Table 2.74.